THE MERGER COEFFICIENT FORMULA BY INCORPORATING PRODUCTION VOLUME FOR THE DESIGN OF A. MODULAR LAYOUT - SISKA (NIM 23406029), MERRY
A modular layout is formed of layout modules which include flow-line layout, cellular layout and functional layout. A modular layout is one of layout that has high flexibility and efficient in material handling flows. The modular layout is designed to minimize the total material handling cost. In this thesis we design a modular layout by using merger coefficient formula which involves production volume of parts. The formula developed is obtained by incorporating the production volume into Huang's merger coefficient formula. Using the case of Huang (2003), the new merger coefficient formula can reduce the total material handling cost by 20.44 % compared to that of Huang's formula and by 6.82 % compared to that of Sunarni's formula. From two cases (namely Case 1 and Case 2) considered, the reductions in the total material handling cost are 21.88 % and 8.64 % for Case 1 and Case 2, compared to those of Sunarni's formula.